Queer theory and diversity management: Reading codes of conduct from a queer perspective - Bendl, Regine; Fleischmann, Alexander; Hofmann, Roswitha (Journal of management & organization, 2009)
Queer theory is a relatively new theoretical approach in organizational discourse that we think can uncover power relations and normative and hierarchical processes in diversity management discourse. ‘Heteronormativity’ and ‘performativity’, core concepts of queer theory, critique categorization and fixed identities and thereby problematize and broaden perspectives on current diversity management discourse, especially those associated with organizational constructions of diversity dimensions. In this article, we focus on the discursive and intersectional construction of subject positions and identities within organizations by drawing upon a queer theoretical framework to analyze three companies' codes of conduct that claim to create an inclusive work environment. The deconstructive analysis of these discursive artifacts emphasizes the intersectional power dynamics of and between the categories of sex, gender and sexuality, and can be taken as a point of departure for questioning the heteronormative arrangements of diversity management practices.